Критичні технології створення робототехнічних комплексів військового призначення - Вирвихвост, О. В. (ХНУРЕ, 2022)
The object of research is military robotic complexes (MRC) used in the system of humanitarian demining. This work is aimed at studying the requirements for MRC. The research is based on the application of a functional approach to the construction of MRC models used in the system of humanitarian demining. It is established that a typical sample MRC can be presented as a set of functionally related elements: base media, mobile platform, specialized equipment, as well as information reception and processing systems, action planning, control systems, automatic pattern recognition, situation analysis, artificial intelligence and training.
Keywords: критичні технології; робототехнічні технології; військові робототехнічні комплекси